2015
DOI: 10.1056/nejmoa1501184
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Adjuvanted Herpes Zoster Subunit Vaccine in Older Adults

Abstract: ConclusionsThe HZ/su vaccine significantly reduced the risk of herpes zoster in adults who were 50 years of age or older. Vaccine efficacy in adults who were 70 years of age or older was similar to that in the other two age groups. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
946
2
33

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,126 publications
(1,007 citation statements)
references
References 32 publications
26
946
2
33
Order By: Relevance
“…Studies revealed that 2 doses of HZ/su containing 50 μg of recombinant VZV glycoprotein E administered at 1-or 2-month intervals were well-tolerated and induced much more robust VZV-specific and VZV glycoprotein E-specific CD4 + T cell and antibody responses than did vOka (55,56). A randomized placebo-controlled study of 15,411 subjects ≥ 50 years of age revealed a remarkable 97.2% efficacy in preventing zoster for a 3.2-year period that did not diminish with increasing age (57). Compared to the placebo group, systemic adverse reactions were 2.2-fold greater in the vaccine group.…”
Section: Gsk Vaccine (Hz/su)mentioning
confidence: 99%
“…Studies revealed that 2 doses of HZ/su containing 50 μg of recombinant VZV glycoprotein E administered at 1-or 2-month intervals were well-tolerated and induced much more robust VZV-specific and VZV glycoprotein E-specific CD4 + T cell and antibody responses than did vOka (55,56). A randomized placebo-controlled study of 15,411 subjects ≥ 50 years of age revealed a remarkable 97.2% efficacy in preventing zoster for a 3.2-year period that did not diminish with increasing age (57). Compared to the placebo group, systemic adverse reactions were 2.2-fold greater in the vaccine group.…”
Section: Gsk Vaccine (Hz/su)mentioning
confidence: 99%
“…HZ/su consists of 50 µg of recombinant VZV antigen (glycoprotein E) which directs the immune response to the virus itself, combined with the AS01B adjuvant system to stimulate T cell immunity to recombinant proteins [106]. As described in detail elsewhere [106], two very large multicenter-blinded RCTs reported that, among participants who had received two doses of Hz/su, VE against zoster was 97.2% (95% CI 93.7–99.0%) for adults aged ≥50 years [107] and 89.8% (95% CI 84.2–93.7%) for those aged ≥70 years [108]. In a pre-specified analysis of data pooled from both trials, the VE against PHN was 88.8% (95% CI 68.7–97.1%).…”
Section: Newer Developments In Zoster Vaccinesmentioning
confidence: 99%
“…While systemic reactions were more commonly reported for the HZ/su vaccine than Zostavax (66.1% [107] versus 24.7% [79]), these adverse effects were transient and around 95% of participants receiving HZ/su in both trials received both vaccine doses. Reassuringly, serious adverse events, immune-mediated diseases and deaths across the entire study period were reported equally between the vaccinated and placebo groups in both ZOE trials.…”
Section: Newer Developments In Zoster Vaccinesmentioning
confidence: 99%
“…The role of zoster vaccination in the very old (>85 years) and immunosuppressed population is as yet unclear. However, some of these problems may be solved by the recent development of a new liposome-based subunit vaccine developed by GlaxoSmithKline [23].…”
Section: Phnmentioning
confidence: 99%